Chest wall reconstruction in benign and malignant tumors with non-rigid materials: An overview - Colella, Sara; Brandimarte, Alessandro; Marra, Roberta; Marinari, Stefano; D’Incecco, Armida; Di Genesio Pagliuca, Milena; De Vico, Andrea; Crisci, Roberto; Divisi, Duilio (Frontiers in Surgery, 2022)
Several materials and techniques have been described for the procedure of chest wall reconstruction: the choice of using a technique or a material over another relies mainly on the surgeon's experience as well as thoracic defect localization and dimension, local availability of materials, and costs. From a technical point of view, autologous and alloplastic reconstruction are available, and, in both cases, rigid and non-rigid prostheses are found. Each material has its peculiarities, with advantages and disadvantages; thus, it is mandatory to be confident when planning the intervention to foresee possible complications and minimize them. We have reviewed the literature on chest wall reconstruction in chest wall tumors (both malignant and non malignant) with non-rigid prosthetic materials, focusing on safety outcomes.